Peri-extubation practices and extubation failure in a South African tertiary paediatric intensive care unit - Kilba, Marie-Charlyne Fatima (Department of Paediatrics and Child Health, 2019)
Objectives To describe the peri-extubation practices in a South African paediatric intensive care unit and to determine the prevalence, risk factors and outcomes of extubation failure. Design Prospective observational study. Setting A multi-disciplinary paediatric intensive care unit in Cape Town, South Africa. Patients All intubated and ventilated patients between May and September 2017. Interventions There were no research- related interventions Measurements and Main Results Extubation failure was defined as requiring re-intubation within 48 hours of planned extubation. Two hundred and sixteen intubations in 204 children, with a median age of 8 months (IQR 1.6 – 44.4) and median PIM3 risk of mortality score 0.03 (IQR 0.01 – 0.07) were included. There were 184 planned extubations; 21 (10.3%) patients died before extubation; two (1%) had tracheostomies; two (1%) were transferred intubated and seven (3.4%) had ventilation withdrawn. Non-invasive ventilation was implemented in 97 cases (52.7%) after planned extubation. There were 21 (11.4%) failed extubations. Indications for re-intubation were: upper airway obstruction (n=7; 33.3%); respiratory failure (n=4; 19.0%); heart failure (n=3; 14.3%); diaphragm paralysis, hypoventilation and cardiac arrest (n=2; 9.5% each); and reduced level of consciousness (n=1; 4.8%). Prematurity (adjusted OR 1.8 (95% CI 0.05 – 0.6); p =0.004), dysmorphology (OR 1.8 (95% CI 0.05 – 0.6); p=0.022), decreased level of consciousness (OR 4.8 (95% CI 1.96 – 11.7); p=0.001) and ventilation ≥48 hours (OR 0.2 (95% CI 0.05 – 0.7); p = 0.003) were independently associated with extubation failure on multivariate analysis. Children who failed extubation had longer duration of ventilation (median 231 versus 53 hours; p < 0.0001), PICU length of stay (median 15 versus 5 days; p < 0.0001) and hospital length of stay (32 versus 15 days; p=0.009); and higher mortality (28.6% versus 6.7%; p = 0.001) compared to those successfully extubated. Conclusion Extubation failure is associated with significant morbidity and mortality. Independent risk factors of extubation failure identified in our context were prematurity, dysmorphology, impaired consciousness and ventilation for more than 48 hours.